Integrating artificial intelligence into thematic learning: The readiness and challenges of teachers at madrasah ibtidaiyah - Nurul Aini; Khaeruddin Said; Baiq Ida Astini (Universitas Papua, 2026)
This study aims to explore the readiness and challenges of Madrasah Ibtidaiyah (MI) teachers in integrating Artificial Intelligence (AI) technology into thematic learning in the era of Education 5.0. This study uses a qualitative approach with field research conducted at MIN 1 Kota Mataram in November 2025, involving six informants selected purposively, consisting of the principal and five classroom teachers. Data were obtained through observation, in-depth interviews, and documentation, then analyzed based on the Miles and Huberman model through the processes of data collection, reduction, presentation, and conclusion drawing, with triangulation as a technique to ensure data validity. The research findings show that MIN teachers already have a basic understanding of AI and show interest in its application, but its implementation is still hampered by limitations in technology-based pedagogical competence, lack of infrastructure, and inadequate institutional support. Nevertheless, the independent efforts of teachers and informal guidance from the principal indicate considerable opportunities for development. This study emphasizes the need for structured training, continuous mentoring, and supportive internal policies to strengthen AI integration, while also serving as a basis for developing a more effective AI training model for MI teachers.